2016
DOI: 10.17475/kastorman.289753
|View full text |Cite
|
Sign up to set email alerts
|

Determining of Some Chemical Properties in Taşköprü Garlic Stored in Different Conditions

Abstract: Geliş Tarihi: 17.06.2016 Özet Sarımsak, kükürtlü bileşikler (alisin, alliin), karbohidratlar (sakkaroz, glikoz), protein, lif ve serbest amino asitler, enzimler, fenolik bileşikler, flavonoitler, β-karoten, vitaminler, makro ve mikro elementler açısından zengin bir bitkidir. Bu nedenle de yıllardır yemeklere lezzet vermek ve birçok hastalığın tedavisinde ilaç olarak kulanılmıştır. Çiğ olarak tüketildiği gibi kurutulmuş sarımsak, sarımsak tozu, sarımsak suyu, sarımsak püresi ve uçucu sarımsak yağı gibi sarımsak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In addition, they are nutritionally important components in food and enhance tolerance to many chronic and some infectious diseases (Elliot et al 2008;Żurawik et al, 2013). It is reported that garlic is an important source of minerals (Turfan et al, 2016;Mardoni, 2017). The mineral profile as macro and micronutrients of the three cloves and bulbs of garlic in this present study are given in Table 4 and Table 5.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…In addition, they are nutritionally important components in food and enhance tolerance to many chronic and some infectious diseases (Elliot et al 2008;Żurawik et al, 2013). It is reported that garlic is an important source of minerals (Turfan et al, 2016;Mardoni, 2017). The mineral profile as macro and micronutrients of the three cloves and bulbs of garlic in this present study are given in Table 4 and Table 5.…”
Section: Resultsmentioning
confidence: 52%
“…SOD activity results are consistent with other studies, Martin et al (2016); Stajner et al (2004) found that Alliaceae member, especially Allium genus had high antioxidant activity. Turfan et al (2016) showed that the SOD values of the garlic were 23.35 EU/mg. Belhadj et al (2015) investigated antioxidant and antimicrobial activities of Allium sativum L. leaves, bulbs and roots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the storage process, lycopene can also be used for the aim of suppressing the increased radical formation in reactions such as oxidation and peroxidation that damage the oxidation sensitive components of the food. A reduction in lycopene content may occur in this situation as well (Eraslan et al, 2007; Oz & Karatepe, 2017; Turfan et al, 2016; Welti et al, 2002). In addition to this, in the freezing process and during the storage of frozen products, the type of fruit, pH, and antioxidant ratio are also stated as the cause of the losses occurring in the properties and concentration of carotenoids (Lisiewska & Kmiecik, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the reduction in the number of antioxidant components, such as β-carotene, which has a function of reducing oxidative damage, may be caused by an increase in malonaldehydes caused by lipid peroxidation and oxidative stress in the storage process (Welti et al, 2002;Eraslan et al, 2007;Turfan et al, 2016;Oz & Karatepe, 2017). In this regard, Oz & Karatepe (2017) made a statement that similar antioxidant mechanisms work to suppress lipid peroxidation and radical formation increase because of protein denaturation.…”
Section: Resultsmentioning
confidence: 99%